Laparoscopic ureteroneocystostomy and round ligament bladder hitching for ureteral stenosis in parametrial deep endometriosis: Our tips for a tension‐free anastomosis. Issue 2 (29th August 2022) - Ianieri, Manuel Maria; Rosati, Andrea; Ercoli, Alfredo; Foschi, Nazario; Campolo, Federica; Greco, Pierfrancesco; Scambia, Giovanni
Abstract: Objective: To investigate the feasibility and the efficacy of laparoscopic ureteroneocystostomy with round ligament bladder hitching. Methods: This is a monocentric retrospective study. Enrolled patients affected by deep endometriosis underwent laparoscopic nerve‐sparing parametrectomy and monolateral ureteroneocystostomy with bladder suspension to the round ligament. Perioperative and postoperative outcomes were collected, as well as urinary and pain symptoms before and after surgery. Results: Laparoscopic ureteroneocystostomy with round ligament bladder hitching was performed in nine women. The most frequent postoperative complication was post‐voiding urinary retention (22.2%). No ureteral fistula or stenosis of the anastomosis was reported. Conclusion: In selected cases of ureteral resection and reimplantation, performing a round ligament bladder hitching allowed us to overcome the ureteral gap. This is a safe and feasible procedure to ensure stability of the anastomosis and avoid the possible disadvantages of the "standard" psoas hitch procedure. Synopsis: In case of ureteral stenosis for deep endometriosis, in selected patients, when a ureteroneocystostomy is required, the round ligament bladder hitching is feasible and safe.